Breather and Pulse-Package Dynamics in Multinonlinear Electrooptical Systems With Delayed Feedback - Alain F. Talla; Romain Martinenghi; Paul Woafo; Yanne K. Chembo (IEEE Photonics Journal, 2016)
We investigate the temporal dynamics of a multinonlinear electrooptical system with delayed feedback. We show that when a self-sustained electronic oscillator is introduced in the electric path of the feedback loop, a wide variety of complex periodic and chaotic states can be excited. In particular, the chaotic breather and pulse-package oscillations with slow–fast temporal dynamics are experimentally observed in the system, and they are characterized by excitablelike trajectories and scroll patterns in the state space. We show that a notable specificity of these chaotic states is the presence of three distinct and well-separated timescales in the temporal time traces. We analyze the interaction between the main nonlinearities of the system and the delayed feedback loop, and finally, we discuss the main dynamical features displayed by this family of photonic systems.